(untitled) (Portuguese Journal of Family Medicine and General Practice, 2023)
Introduction: Intestinal spirochetosis (IE) is a condition defined by the presence of spirochetes on the surface of the colonic mucosa. The implicated organisms can be Brachyspira aalborgi or Brachyspira pilosicoli. Its prevalence is low in developed countries and a higher incidence has been described in homosexuals and people with the human immunodeficiency virus (HIV). This case aims to show the diagnosis of this pathology in an immunocompetent patient and its correct treatment. Case description: Female, 63 years old, retired, with a medical history of excess weight, hypertension, dyslipidemia, and mild mitral and tricuspid regurgitation. She went to an appointment due to watery diarrhea after a month of evolution. Additionally, she drinks water from the well. She denied abdominal pain, nausea, vomiting, weight loss, melena, or hematochezia. In this context, the patient was submitted to a colonoscopy, which showed nonspecific segmental colitis of probable infectious etiology. Biopsies revealed mild and nonspecific inflammatory changes and, in some fragments, colonization of the epithelial surface by bacteria with typical IE morphology. Due to these findings, an analytical study was performed, including serological evaluation for HIV and syphilis, which were negative. Treatment with clarithromycin and metronidazole was started, with the resolution of symptoms. Comment: This clinical case aims to alert to an uncommon pathology in primary health care, namely in immunocompetent patients. The family physician needs to be knowledgeable and aware of the different etiologies of chronic diarrhea for a correct and timely diagnosis and treatment.